A novel fault tolerant control approach based on backstepping controller for a five phase induction motor drive: Experimental investigation. (June 2021) - Mossa, Mahmoud A.; Echeikh, Hamdi
Abstract: The five phase induction motor (FPIM) is a very suitable choice for different industrial applications which require high reliability. This is due to the ability of the motor to keep operating even with open stator phases. However, to ensure the right operation and for achieving the desired dynamic performance in terms of reduced torque fluctuations, a fault tolerant control (FTC) methodology must be applied. Because of this, the paper introduces a novel FTC approach for the FPIM drive based on a backstepping controller. The derivation and explanation of the proposed technique are presented and analyzed in a systematic manner. The validation of the proposed FTC strategy has been carried out experimentally using a dSPACE 1104 control board. The test results approve the validity of the designed controller in achieving the control targets which ensures the highest system reliability of the drive that is mostly required in different automotive and industrial applications. Highlights: Multiphase motor drives. Design of five-phase induction motor in healthy and faulty operation conditions. Fault tolerant control of five-phase induction motor. Nonlinear backstepping controller. Experimental validation.